2014
DOI: 10.1002/bies.201400131
|View full text |Cite
|
Sign up to set email alerts
|

Atlas stumbled: Kinesin light chain‐1 variant E triggers a vicious cycle of axonal transport disruption and amyloid‐β generation in Alzheimer's disease

Abstract: Substantial evidence implicates fast axonal transport (FAT) defects in neurodegeneration. In Alzheimer's disease (AD), it is controversial whether transport defects cause or arise from amyloid-β (Aβ)-induced toxicity. Using a novel, unbiased genetic screen, Morihara et al. identified kinesin light chain-1 splice variant E (KLC1vE) as a modifier of Aβ accumulation. Here, we propose three mechanisms to explain this causal role. First, KLC1vE reduces APP transport, leading to Aβ accumulation. Second, reduced tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“… also suggested that APP‐containing vesicles transported by kinesin‐1 suppressed Aβ generation. Furthermore, recent reports indicated that the kinesin light chain‐1 splice variant E (KLC1vE) is an Aβ accumulation modifier that triggers a vicious cycle of axonal transport disruption in AD . Here, our work demonstrated that KLCs inhibited Aβ 42 aggregation at the single‐molecule level in vitro as determi‐ned by DC‐FCCS.…”
Section: Resultsmentioning
confidence: 60%
“… also suggested that APP‐containing vesicles transported by kinesin‐1 suppressed Aβ generation. Furthermore, recent reports indicated that the kinesin light chain‐1 splice variant E (KLC1vE) is an Aβ accumulation modifier that triggers a vicious cycle of axonal transport disruption in AD . Here, our work demonstrated that KLCs inhibited Aβ 42 aggregation at the single‐molecule level in vitro as determi‐ned by DC‐FCCS.…”
Section: Resultsmentioning
confidence: 60%
“…Audouard et al (101) recently showed that disrupted axonal transport precedes progressive muscle denervation in mice expressing pathogenic human tau, while Stevenson et al (102) used squid giant axon to show that amyloid precursor protein interacts at the organelle/microtubule interface, possibly mediating vesicular transport and Alzheimer's pathology. Gan et al (103) proposed that the disruption of axonal transport by a mutant kinesin light chain-1 splice variant in Alzheimer's disease follows a progression of reduced axonal transport, which leads to accumulation of protein aggregates, followed by an ER stress response. These examples illustrate that the literature is growing at a rapid pace, with novel mechanistic hypotheses pushing the field toward a better understanding of etiology and potential therapeutics.…”
Section: Microtubule Defects In Nervous System Diseasementioning
confidence: 99%
“…The recruitment of kinesin-1 to APP via KLC1vE could alter trafficking of APP through the compartments responsible for amyloidogenic cleavage. Alternatively, KLC1vE could more efficiently recruit JNK to APP, and facilitate the phosphorylation conducive of secretase cleavage [70]. These scenarios highlight the numerous ways by which APP transport and processing are entangled.…”
Section: Factors That Regulate the Transport Of App Also Regulate Itsmentioning
confidence: 99%